KAJIAN PERGERAKAN SEDIMEN DASAR DAN GERUSAN PADA SALURAN LURUS ALLUVIAL - Azwarman Azwarman (Universitas Batanghari Jambi, 2013)
The movement of sediment on straight channel especially on altitude area with the alluvial, scour sediment or erosion as well transportation sediments influential to change the form of channel is very .If we see the day of the day flow on the basis of the move will undermined if the speed flow produce voltage critical shear, exceed speed and voltage shear allowable .Scour sediment larger on the stream velocity around the bend if compared to channel on straight .Big and small scour sediment depent also to stream velocity at the channel and also depend kinds of the material .Reseach done on straight up for flow in twist destroy the outside of the bend channel cliff always ,while on the part in the corner occured and large depositional hangs from the discharge of channel and morpologinya alittle depotional .Length of time jetting to achieved equilibrium (stabile) .Stabile condition achieved where there is balance between the sediment carried over with sediment incoming balanced and changes shape cross section almost nothing . On probation review channel alluvial this made six different jetting time .but the discharge of the sama with q=0,00354 m3/det and D50=0,0004 and the tools sower of sand(sandfeeder) the installed on upstream channelKey words : discharge, material ,time equilibrium,stream velocity